Settlement Disputes on Land Right Between Factory and Farmers Through Agrarian Reforma - Rachmah Risandi (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
The specific object in this research is Land Rights Dispute Settlement between PT. Karyadeka Alam Lestari with Farmers in Trisobo Village, Boja District, Kendal Regency through Agrarian Reforma with the formulation of the problem: (1) Why is there a dispute over tenure over land rights between PT. Karyadeka Alam Lestari with Farmers in Trisobo Village, Boja District, Kendal Regency? (2) What is the settlement of land rights tenure disputes between PT. Karyadeka Alam Lestari with farmers from Trisobo Village, Kendal Regency by the Regional Office of the National Land Agency of Central Java Province, is in accordance with the National Land Law? (3) What are the obstacles faced by the Regional Office of the National Land Agency of Central Java Province in resolving land tenure disputes between PT. Karyadeka Alam Lestari with farmers from Trisobo Village, Kendal Regency? (4) What is the follow-up to the settlement of land rights tenure disputes between PT. Karyadeka Alam Lestari with farmers from Trisobo Village, Kendal Regency through Agrarian Reforma? This study uses an empirical juridical approach with explanatory analysis research specifications. Primary data of this study were obtained from interviews with Central Java Provincial Office, Kendal District Land Office, PT. Karyadeka Alam Lestari and the head of Trisobo village using the snowball sampling method. The data collection techniques used were library studies and field studies. The data analysis technique used descriptive qualitative. The results of the research are: (1) The occurrence of land rights tenure disputes between PT. Karyadeka Alam Lestari with Farmers in Trisobo Village, Boja District, Kendal Regency because of the social disparity between Trisobo Village farmers and PT. Karyadeka Alam Lestari. (2) Settlement of land rights tenure disputes between PT. Karyadeka Alam Lestari with farmers from Trisobo Village, Kendal Regency, by the Regional Office of the National Land Agency of Central Java Province, is in accordance with the National Land Law. (3) The obstacle faced by the mediator is in providing a correct legal understanding of land control to the disputing parties. (4) The follow-up action taken by the Regional Office of the National Land Agency of Central Java Province is to determine a portion of the land object of the dispute covering an area of 11. 5 Ha is state land released by PT. Karyadeka Alam Lestari to Trisobo village and used as land Reforma land objects which will be redistributed to 570 farmer families in Trisobo Village, Boja District, Kendal Regency through the Agrarian Reforma program.